Chemically Defined and Xeno-Free Cryopreservation of Human Adipose-Derived Stem Cells - López, Melany (PLoS One, 2016)
The stromal compartment of adipose tissue harbors multipotent cells known as adipose-derived stem cells (ASCs). These cells can differentiate into various lineages including osteogenic, chrondrogenic, adipogenic, and neurogenic; this cellular fraction may be easily obtained in large quantities through a clinically safe liposuction procedure. Therefore, ASCs offer exceptional opportunities for tissue engineering and regenerative medicine. However, current practices involving ASCs typically use fetal bovine serum (FBS)-based cryopreservation solutions that are associated with risks of immunological reactions and of transmitting infectious diseases and prions. To realize clinical applications of ASCs, serum- and xeno-free defined cryopreservation methods are needed. To this end, an animal product-free chemically defined cryopreservation medium was formulated by adding two antioxidants (reduced glutathione and ascorbic acid 2-phosphate), two polymers (PVA and ficoll), two permeating cryoprotectants (ethylene glycol and dimethylsulfoxide), a disaccharide (trehalose), and a calcium chelator (EGTA) to HEPES-buffered DMEM/F12. To limit the number of experimental groups, the concentration of trehalose, both polymers, and EGTA was fixed while the presence of the permeating CPAs and antioxidants was varied. ASCs suspended either in different versions of the defined medium or in the conventional undefined cryopreservation medium (10% dimethylsulfoxide+10% DMEM/F12+80% serum) were cooled to -70°C at 1°C/min before being plunged into liquid nitrogen. Samples were thawed either in air or in a water bath at 37°C. The presence of antioxidants along with 3.5% concentration of each penetrating cryoprotectant improved the freezing outcome to the level of the undefined cryopreservation medium, but the plating efficiency was still lower than that of unfrozen controls. Subsequently, increasing the concentration of both permeating cryoprotectants to 5% further improved the plating efficiency to the level of unfrozen controls. Moreover, ASCs cryopreserved in this defined medium retained their multipotency and chromosomal normality. These results are of significance for tissue engineering and clinical applications of stem cells.